THE USE OF PICTURE SERIES FOR TEACHING WRITING OF RECOUNT TEXT - Mutmainnah, Mutmainnah; Rufinus, Albert; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to investigate whether or not the use of picture series affect the students’ writing of recount text and to find out the effect size of the improvement of students’ writing of recount text after being taught using picture series of the tenth grade students of SMA Negeri 5 Pontianak. The form of this research is pre-experimental study with one group pre-test and post-test design. The population of this research is the tenth grade students of SMA Negeri 5 Pontianak, while the sample is class X A that consists of 32 students. The research findings show that the mean score of pre-test is 59.41 while the mean score of post-test is 69.16. It shows that picture series improves the students’ writing of recount text. The result of this research shows that t-test is higher than t-critical the value is 5.512.042. It means that the alternative hypothesis (Ha) is accepted. It can be concluded that there is a highly significant effect of the use of picture series for teaching writing of recount text on the tenth grade students of SMA Negeri 5 Pontianak. Keywords: Picture Series, Teaching Writing, Recount Text